Intelligent transport system for motorcycle safety and issues - Ambak, Kamarudin; Atiq, Riza; Ismail, Rozmi (EuroJournals Publishing, 2009)
This paper provides a review of Intelligent Transport System for motorcycles safety and related issues with some existing or emerging ITS technologies to enhanced vehicles safety. Intelligent Transport Systems (ITS) have significant potential to enhance traffic safety. Numerous ITS technologies have been developed to improve the safety and efficiency of cars, commercial vehicles, public transport and infrastructure. ITS applications have been developed with car safety in mind, but the potential for developments for motorcycle is great. Very few ITS have been developed specially for motorcycles, and all of those that do exist are in-vehicle systems. Many ITS exist or are emerging for other classes of vehicle that have potential to enhance motorcycle safety directly or indirectly. There several ITS technologies in-vehicle system to be introduced and adapted to motorcycles; advanced driver assistance system, intelligent speed adaptation, driver monitoring system, collision warning and avoidance system, lane keeping and lane-change warning system, visibility enhancing system, seat belt/helmet reminder system. However, there is a need for the development of standards for the design of ITS technologies for motorcycles, as there is for the design of ITS technologies for other vehicles. Motorcycle pose particular problem when it comes to the technical adaptation of certain ITS systems, particularly those that have not been custom-designed for motorcycle.